Determinants and implications of improving partnership relations in cooperation between suppliers of metal products and a digital marketplace company operating on the marketproduction on contract - Górska Monika (2022)
The metal sector is one of the important links in the whole economy. As there is strong competition in this market, companies need to constantly adapt to changes in the environment to maintain their position. For this reason, companies are looking for new solutions to improve their functioning both in the internal - organizational and technical area, as well as in the external area - i.e., the involvement of external entities - customers and partners. Functioning on the market is associated with the need for both short and long-term cooperation with distributors, suppliers, consulting companies, and subcontractors, and the growth in this area, i.e., external growth, as shown by the last several years and the success of many companies operating within the sharing economy, is more important than the internal development of the company itself. Therefore, one of the basic factors contributing to success is shaping cooperation with market participants. The article presents the way of functioning and the possibilities of improving relations between the company and partners to offer products or provide services with the greatest possible innovation. The study aimed to evaluate and analyse the cooperation of a Digital marketplace operating in the production market on commission with production partners, with particular emphasis on the impact of partner relations on its functioning. The subject of the study was a company dealing with the digitization of the traditional production process on commission using a distributed network of production partners (distributed production). The form of the so-called digital marketplace forces the examined company to constantly improve the tools that enable the provision of its services to potential buyers and suppliers. Therefore, the appropriate selection of methods and tools by the examined company may significantly affect the conditions and motives for the cooperation of the company's production partners, which was justified by the results achieved. The article contains a literature analysis on cooperation and partner relations with suppliers in distributed production. The reasons for undertaking cooperation by companies and their effects are presented, referring these issues to the realities of the metal market. The results of the survey were also presented, describing the factors influencing the decision to cooperate with a Digital marketplace operating on the production market commissioned by suppliers, with particular emphasis on the need to improve their relations.